ANALYSIS OF THE DISTRIBUTION OF BODY FLUIDS VOLUMES IN PATIENTS WITH ACUTE CORONARY PATHOLOGY WITH REGARD TO REMODELING OF THE LEFT VENTRICLE MYOCARDIUM - M. M. Batiushin; E. O. Golovinova; E. S. Levickaja; L. I. Rudenko; A. V. Hripun (Архивъ внутренней медицины)
Purpose: estimation  of the dynamics of distribution of the organism water environment in patients with acute coronary syndrome (ACS) taking into account the presence of myocardial hypertrophy of left ventricle, at different stages of hospitalization. Materials and methods: we have examined 120 patients  with ACS undergoing restoration of coronary blood flow. The assessment was made traditional and renal risk factors (albuminuria 30-300 mg/l, the value of eGFR), and produced the aqueous environments  of the body. All examined patients  were divided into two groups. The first group includes patients  with left ventricular hypertrophy, the second group included patients  without hypertrophy of the LV myocardium. Results: for both studied groups were characterized  by the increase in the total  water volume (TWV), the total  liquid volume (TLV), the intracellular fluid volume (IFV) at all stages of the study. Summary: in patients with ACS and the presence of LV hypertrophy found a significant increase of the average content  of TWV,  TLV, IFV at all stages of hospitalization. Also in the group of patients  with LV remodeling and hyperhydratation was observed a decrease in GFR, and the presence of albuminuria.